Evolução hidrotermal e gênese do depósito de Cu-Au Corpo Sul, Arco Magmático de Mara Rosa, Goiás, Brasil - Lopes, Patricia Tatiane, 1984- (2024)
Orientadores: Roberto Perez Xavier, Wagner da Silva Amaral